Ensiklopedia Mukjizat Al-Qur'an Dan Hadis Jilid 4: Kemukjizatan Psikoterapi Islam - [Tidak Terdaftar] (Sapta Sentosa, 2009)
Ensiklopedia Mukjizat Al-Qur'an Dan Hadis Jilid 4: Kemukjizatan Psikoterapi Islam